TEACHERS’ PERCEPTIONS ON ADOPTING E-LEARNING DURING COVID-19 OUTBREAKS; ADVANTAGES, DISADVANTAGES, SUGGESTIONS - Balqis Husain; Yenita Natasya Idi; Megawati Basri (UIN Sumatera Utara Medan, 2020)
This study is to know the teachers' perception of adopting a virtual classroom during a pandemic and discover the conveniences, obstacles, and suggestions when e-learning is being carried out. Sort of this research was qualitative using descriptive method. The method of choosing respondents used convenience sampling. Data collection used questionnaires and open-ended questions. Junior and senior high school teachers in North Maluku were respondents in this research. The subjects of this study were 92 respondents. To analyze the data using SPSS 17. Based on the finding, it found that majority of the teachers used several platforms for online home study during the lockdown. Either Single types of platforms or mixed e-learning was used to gain maximum results in instructional activity. Nine list advantages were addressed on e-learning; in the contrary, it also produced seven barriers. Additionally, the educators offered attractive and innovative ideas to tackle numerous obstacles among educators, students, and educational institutions